Defining timeliness in care for patients with lung cancer: protocol for a scoping review. Issue 11 (4th November 2020) - Ansar, Adnan; Lewis, Virginia; McDonald, Christine Faye; Liu, Chaojie; Rahman, Aziz
Abstract : Introduction: Cancer is the second leading cause of death worldwide, and lung cancer is the single leading cause of cancer mortality worldwide. Early diagnosis of lung cancer is the key to better prognosis and longer survival. While there are substantial literature reporting delays in cancer diagnosis, there is a lack of consensus in the definitions and terms used to describe 'delay' in the treatment pathway. The aim of this scoping review is to identify and critically synthesise the operational definitions and terminologies used to describe the timely initiation of care and consequent treatments over the care pathway for patients with lung cancer. This scoping review will also compare how timeliness was operationalised in Western and Asian countries. Methods and analysis: The scoping review will use the methodology described by Arksey and O'Malley and endorsed by the Joanna Briggs Institute. MEDLINE, EMBASE, CINAHL and PsycINFO electronic databases will be searched. Grey literature sources and the reference lists of key studies will be used to identify additional relevant studies. The scoping review will include all studies, irrespective of study methodology and quality. Two reviewers will independently screen all titles and abstracts to identify eligible studies for inclusion. The full texts of identified studies will be further examined and charted using a data extraction form. A narrative synthesis will be performed to assess and categorise available definitions of timeliness. Ethics and dissemination: Ethical approval is not needed as this scoping review will be reviewing already published articles. The results produced from this review will be submitted to a scientific peer-reviewed journal for publication and will be presented at scientific meetings.